PENGARUH KOMUNIKASI PEMASARAN TERPADU DAN EKUITAS MEREK TERHADAP LOYALITAS KONSUMEN (STUDI PADA HOTEL DYAN GRAHA PEKANBARU) - Situmorang, Sintike; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Integrated marketing communication is the company's efforts to inform, persuade, and remind consumers of the company's brands and products. The consistent and effective Integrated marketing communicationis can awaken and remind consumers of the existence of a product and can also grow the brand equity. Brand equity is a set of beliefs and impressions that consumers have of a company. A good and positive brand equity is a competitive advantage in realizing the company's goals. Success in realizing the company's goals starts from the consumer's loyalty to make a buy back. Repurchase intention is the desire of consumers to buy back a product or service based on the impression and experience of a consumer to a company.This research was conducted at Hotel Dyan Graha Pekanbaru which located at Gatot Subroto No. 07 Pekanbaru. The problem in this research is not achieving the company's sales target in the last five years and the percentage of sales target achievement decreased in three consecutive years and the least increase of consumer number. This is allegedly influenced by customer loyalty.The purpose of this study is to determine the effect of Integrated marketing communicationis and brand equity on the customer loyalty at Hotel Dyan Graha Pekanbaru. In this research the method used is descriptive quantitative with SPSS program. The sample of this study was taken as many as 100 respondents from the total population 141.938 calculated using slovin formula. Methods of data collection using questionnaires. Hypothesis testing using multiple linear regression analysis method.The results showed that the Integrated marketing communicationis and the brand equity have a positive and significant effect on customer Loyalty at Hotel Dyan Graha Pekanbaru.Keywords: Integrated Marketing Communication, Brand Equity, CustomerLoyalty.